Soviet Nomenclature and Exclusive Consumption: from Privileges to Illegality - Ivanauskas , Vilius (Genocidas ir rezistencija, 2014)
Soviet nomenclature includes people in leading positions, the Soviet elite, decision-makers of the period, and people responsible for organising the policies of the Communist Party and empowered to formulate aims and requirements on a variety of levels. Yet, it is not their political power, but rather their publicly visible privileges within the context of social relations that made the Soviet nomenclature the elite group of Soviet society. This exclusivity was based on privileges and better consumption opportunities – features which made it very clear as to who belonged to the nomenclature and who did not. The main thesis of this article is that the Lithuanian nomenclature in Soviet times was the group of society granted with exclusive consumption opportunities and privileges. Both the official support of the regime and informal (illegal) methods formed on the basis of mutual relationships within the nomenclature ensured its welfare and provided conditions for them to act. The concept of “exclusive consumption” seeks to define the field of consumption opportunities available to the nomenclature in the Soviet system, to detail individual privileges and provide examples of goods or services essentially available only to the nomenclature and the extent of those privileges, and to reveal the importance of such consumption to the status of the nomenclature in the Soviet system. Two lines of “exclusive consumption” of the nomenclature are identified in this respect. The first line illustrates how the state in the Soviet system established the boundaries dividing the nomenclature from non-nomenclature. The structurally established barrier destroyed all the government’s attempts to create an egalitarian society declared in the official discourse. The second line emphasises the manner of acting which was typical to a considerable part of the nomenclature – the ability to manoeuvre and, on the basis of the position held and established connections, to expand their consumption, thus contributing to the dissemination of this manner of acting as a much sought after model in the Soviet system.